3. ANALISIS PENGENDALIAN PERSEDIAAN LOW DENSITY POLYETHYLENE (LDPE) DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) PRODUK CAIRAN INFUS DI PT. WIDATRA BHAKTI - Malang, Sekolah Tinggi Ilmu Administrasi (STIA) (Ilmu Administrasi, 2019)
AbstractPT. Widatra Bhakti is a pharmaceutical company engaged in producing basicinfusion fluids whose 99% of the products are intended for the domestic market and 1%for overseas markets. In conducting its production activities are closely related to thesupply of raw materials which are important components that must be available for thesmoothness of the production process. The raw material used is LDPE, which is used forthe process of making the infusion bottles. This study aims to determine the control ofLDPE raw material inventory at PT. Widatra Bhakti and to determine the amount ofeconomical ordering of LDPE raw materials as well as to determine the minimum totalinventory cost. This research uses descriptive method that is quantitative because thisresearch relates to the object of research that is on the company with a certain period oftime by collecting data and information relating to the company and suited to the purposeof the research. Descriptive analysis techniques used to analyze data on LDPE rawmaterial inventory control problem in an effort to reduce the inventory cost usingEconomic Order Quantity (EOQ) method. The result shows that the company can savecosts with fewer purchase frequencies if the EOQ method is used where inventory costsare more cost-effective than using current company-run methods is used.Keywords: Inventory Control, EOQ, Inventory Cost